Ecological instability in Upper Cambrian-Lower Ordovician trilobite communities from Northwestern Argentina - Balseiro, Diego (2012)
Although ecological stability has been widely studied in the fossil record, it has seldom been analyzed in trilobite dominated communities. We test stability in these communities from the Upper Cambrian–Lower Ordovician of the Cordillera Oriental, Northwestern Argentina. The studied interval spans approximately 5 ma. and for this analysis it was divided in four smaller scale informal intervals of approximately 1.5 to 2 ma. Sampling covers a wide geographic area of ~ 7000 km2 in each time bin. In order to analyze ecological stability, we tested for patterns predicted from the hypothesis of coordinated stasis and habitat tracking. For the analysis of coordinated stasis we studied taxonomic turnover. Migrations and evolutionary turnovers based on the regional and global occurrence of taxa were assessed. Results indicate important rates of immigration and emigration, highlighting the relevance of migration in the assembly of the meta-community. The percentage of carryovers and holdovers was variable between intervals and did not show a bimodal pattern, contradicting the coordinated stasis model. In addition, an ordination analysis performed with correspondence analysis suggests that each interval has an idiosyncratic genus composition. In order to test the model of habitat tracking, an analysis of the stability of biotic gradients and the environmental fidelity of stenotopic taxa was conducted. We carried out a Mantel test to analyze the recurrence of taxa present in different intervals. The results showed that taxa are grouped differently in every interval, indicating instability of biotic gradients. We also performed a gradient analysis for each interval and compared intervals with each other using a Procrustes analysis. Results of this analysis indicate that taxa respond individualistically to environmental changes. Moreover, high Procrustes errors are present in rare taxa. Because rarity is largely related to niche breadth, this result suggests that many stenotopic taxa had little environmental fidelity. Overall, this study suggests that migration appears to be of great importance in the composition of local and regional communities, and that the biotic gradients formed in each interval had a distinct composition and structure. Such compositional and ecological instability do not show convincing evidence to support coordinated stasis. Finally, the concept of individualistic habitat tracking is more clearly understood in light of metacommunity processes such as dispersal and habitat preferences, rather than as a process by itself.